Molecular Diagnostics for Precision Medicine in Colorectal Cancer: Current Status and Future Perspective. (6th September 2016) - Chen, Guoli; Yang, Zhaohai; Eshleman, James R.; Netto, George J.; Lin, Ming-Tseh
Abstract : Precision medicine, a concept that has recently emerged and has been widely discussed, emphasizes tailoring medical care to individuals largely based on information acquired from molecular diagnostic testing. As a vital aspect of precision cancer medicine, targeted therapy has been proven to be efficacious and less toxic for cancer treatment. Colorectal cancer (CRC) is one of the most common cancers and among the leading causes for cancer related deaths in the United States and worldwide. By far, CRC has been one of the most successful examples in the field of precision cancer medicine, applying molecular tests to guide targeted therapy. In this review, we summarize the current guidelines for anti-EGFR therapy, revisit the roles of pathologists in an era of precision cancer medicine, demonstrate the transition from traditional "one test-one drug" assays to multiplex assays, especially by using next-generation sequencing platforms in the clinical diagnostic laboratories, and discuss the future perspectives of tumor heterogeneity associated with anti-EGFR resistance and immune checkpoint blockage therapy in CRC.